Crowdworking in France and Germany - Chiara Belletti; Daniel Erdsiek; Ulrich Laitenberger; Paola Tubaro (ZEW - Leibniz Centre for European Economic Research, 2021)
Crowd work refers to the practice of assigning tasks and projects undertaken for payment to online contributors via digital platforms. We use data from a recent survey among companies in Germany and France to explore the economic relevance and potential barriers of this phenomenon from the demand side. In particular, companies from the information economy and the manufacturing industry have been surveyed in Germany and companies from the manufacturing, construction, and services and trade industries were surveyed in France. Specifically, we provide evidence on the share of companies using crowd work and investigate what incentivises or hinders companies' decisions to hire online contributors on digital platforms. Despite some differences between both countries, we identify trends for Germany and France.
Keywords: 330; Telearbeit; Digitale Plattform; Arbeitsgestaltung; Arbeitsbedingungen; Personalmanagement; Deutschland; Frankreich